Species Composition Diversity of Chlorophyta and Charophyta Phyla in Bach Ma National Park, Thua Thien Hue Province - Ha, Le Thi Thuy; Tu, Hoang Thi Ngoc; Oanh, Cao Thi Tu; Ngan, Nguyen Thuy; Quynh, Nguyen Thi Thuy (VNU Journal of Science: Natural Sciences and Technology; Vol 38 No 3DO - 10.25073/2588-1140/vnunst.5221, 2022)
This study was conducted to investigate the species composition of Chlorophyta and Charophyta in Bach Ma National Park, Thua Thien Hue province. Here, we identified 45 species and subspecies, belonging to 17 genera, 7 families, and 4 orders. Charophyta was the most diverse phylum, with 75.56% total species. The dominant orders and families are Desmidiales and Desmidiaceae. The most diverse genus belongs to Cosmarium (15), Euastrum (5) and Scenedesmus (5). Micrasterias foliacea Bailey ex Ralfs and Cosmarium pardalis Cohn are tropical algae, while transitional species and temperate species are also present such as Cosmarium pachydermum Lund. var. indicum Iyenf. et Vim Bai and Euastrum jenneri W. Archer, respectively. The dominant group is described as Desmidiales with Chlorococcales (Ch. I) index ranging from 0.087 to 0.19 in Thuy dien Dam and Thuy dien bridge, while there are several species of Sphaeropleales with Ch. I index of 0.67 in Hoang Yen stream.